Spritualitas Filsafat Kontemporer (Memahami "Peran" dan "Relevansi" dalam Evolusi Kehidupan) - Joko Siswanto (Jurnal Filsafat "WISDOM", 2006)
The confusion of modern spirituality’s vision thought out a cultural model that destitute and insulted the sacred meaning oflife. Such situation expressed new awareness for the group ofcontemporary philosopher in rethinking a new vision of life. The new spirituality’s vision that presented by Chardin,Whitehead, and Marcel is an effort regarded to understand thecharacter and God’s relevance with the evolution of life. The newspirituality is drawn as a concrete thing or materialized. This newspirituality is often viewed in the contradictory with classical ideasof immaterialized transcendence. This kind of opinion is not true atall; because the contemporary spirituality is not an unwilling ofeverlasting truth of the transcendence vision of Allah, but thespiritual energy should be erected in nature, body, and societywhich are reflected as mystery mediation.